2020
DOI: 10.1186/s13018-020-01739-x
|View full text |Cite
|
Sign up to set email alerts
|

Melone’s concept revisited in comminuted distal radius fractures: the three-dimensional CT mapping

Abstract: Background: There is no consensus in the literature about the ideal classification of the distal radius fracture for the clinical practice. The traditional Melone classification system divides the distal radius into four basic components, the shaft, radial styloid, dorsal medial fragment, and volar medial fragment. The aim of this study was to identify fracture lines in comminuted distal radius fractures using three-dimensional mapping of computed tomography (CT) images to test the hypothesis that fracture fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…In 23 association for osteosynthesis (AO) C3 DRFs, Li et al (2020) found the mean 'volar medial' fragment CSA was 1.5 cm 2 (SD 0.8), consistent with our study where the mean CSA for all fragment types was 1.6 cm 2 (SD 0.7). After defining three PUC fragment types based on morphological data, each had significantly different articular CSAs.…”
Section: Discussionsupporting
confidence: 91%
“…In 23 association for osteosynthesis (AO) C3 DRFs, Li et al (2020) found the mean 'volar medial' fragment CSA was 1.5 cm 2 (SD 0.8), consistent with our study where the mean CSA for all fragment types was 1.6 cm 2 (SD 0.7). After defining three PUC fragment types based on morphological data, each had significantly different articular CSAs.…”
Section: Discussionsupporting
confidence: 91%
“…However, more basic work is needed to realize intelligent expert. Due to the increasing focus on big data analysis, 3D CT-based fracture mapping has been widely used in the field of orthopedics, such as the fracture characterization of proximal femur [8], tibial plateau [11,12], distal radius [13], or patellar [14], as originally described by Cole et al [6]. In our study, we have firstly described the fracture lines and morphological features of distal humeral fractures by three-dimensional mapping technology.…”
Section: Discussionmentioning
confidence: 94%
“…A three-dimensional fracture map can demonstrate the characteristic of fracture morphology and has been used to study fractures in distal radius [ 17 ], intertrochanter, distal femur [ 4 ], patella [ 18 ], tibial plateau [ 19 ], and ankle [ 20 ], providing more details and the overall characteristics of fractures compared to plain radiography or two-dimensional CT images. Based on the 3D fracture map, the fracture heat map also displays the fracture incidence of each part.…”
Section: Discussionmentioning
confidence: 99%